2005
DOI: 10.1007/bf02762968
|View full text |Cite
|
Sign up to set email alerts
|

Estimation in conditional first order autoregression with discrete support

Abstract: Bias correction, Estimation, INAR models, Overdispersion, Small sample properties, Time series of counts,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…. , X T , model estimation can be done, among others, by the following three approaches; see also Al-Osh and Alzaid (1987) and Jung et al (2005). First, the model parameters can be estimated by the method of moments (MM), i.e., the parameters are estimated from empirical mean, variance and first-order autocorrelation, considering the relations of Table 2.…”
Section: Binomial Thinning and Generalized Thinningmentioning
confidence: 99%
See 1 more Smart Citation
“…. , X T , model estimation can be done, among others, by the following three approaches; see also Al-Osh and Alzaid (1987) and Jung et al (2005). First, the model parameters can be estimated by the method of moments (MM), i.e., the parameters are estimated from empirical mean, variance and first-order autocorrelation, considering the relations of Table 2.…”
Section: Binomial Thinning and Generalized Thinningmentioning
confidence: 99%
“…Corresponding standard errors can be computed from the observed Fisher information. An extensive comparative study of properties and performance of these and different types of estimators was provided by Jung et al (2005).…”
Section: Binomial Thinning and Generalized Thinningmentioning
confidence: 99%
“…We restrict to the period from January 1994 to December 2002 (108 observations), which was already investigated by (Jung et al, 2005). A line plot of the data is shown in Figure 4 (a),…”
Section: Simultaneous Confidence Regionsmentioning
confidence: 99%
“…(Jung et al, 2005) fitted a Poisson INAR(1) model to the data, but since the estimates obtained with different methods deviated heavily from each other, they concluded that such a model is not appropriate. And in fact, see (Jung et al, 2005), the data exhibits overdispersion (the empirical variance equals 7.92, being much larger than the mean 4.94), making the Poisson marginal distribution an unreasonable choice, also see Figure 4 (d).…”
Section: Simultaneous Confidence Regionsmentioning
confidence: 99%
“…The INAR model has been extensively studied in the literature. For example, see the survey by Weiß, [3] Jung et al [4] and Freeland and McCabe. [5] Monteiro et al [6] had proposed the The process {Y t } t∈Z in Equation (1) has two random components: the survivors of the elements of the process at time t − s, given by φ • Y t−s , each with probability φ of survival, and the elements which entered the system in the interval (t − s, t], defining the innovation term ǫ t .N o t e that the INAR(1) model [2] is a particular case of the INAR(1) s when s = 1.…”
Section: Introductionmentioning
confidence: 99%